Mental Health and Covid-19 Situation - Kalita, Jagabandhu (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The main aim of mental hygiene- is to attain good mental health. Mental health is an important part of overall health and wellbeing. The beginning of mental hygiene- movement in the west may be too traced to the first decade of the present Century. This paper is mainly focused on the mental health problems, causes and to create awareness among the people during the covid-19 situation. Secondly, it also discuss how we can cope with this stressful covid situation. This is a theoretical paper and data are collected from the secondary sources and descriptive method has been used.